Studying investor rationality on stock price: A case of Bank Syariah Indonesia - Kresnaputra, Hafidz Yudhanto; Kafabih, An'im (Faculty of Economics, Universitas Islam Indonesia, 2025)
Purpose – This study aims to analyze the behavior of investors' investment decisions, as reflected in the volatility of stock prices, especially at PT Bank Syariah Indonesia Tbk (BSI). The analysis here compares aspects of rationality and irrationality as well as their relationship with the stock prices of Bank Syariah Indonesia.Methodology – This study uses the Autoregressive Distributed Lag (ARDL) method to test aspects of rationality proxied by Price-to-Book Value (PBV) and Price-to-Earnings Ratio (PER), while aspects of irrationality proxied by mood sentiment (SWAV). Data were collected from February 2021 to February 2024 on a monthly basis, resulting in 37 research samples.Findings – The results show that PBV, PER, and mood sentiment have a significant effect on BSI stock prices. In the long term, PBV has a positive effect, while PER and mood sentiment have negative effects on BSI stock prices. In this situation, mood sentiment has the greatest influence on BSI stock prices, indicating that the volatility of BSI stocks is driven by irrationality.Implications – As the stock price is driven mostly by irrationality, investors must have fundamental and macroeconomic analysis skills as well as expertise when buying and selling stocks in order to minimize losses due to the irrational behavior. In addition, regulators and companies must provide transparent and accurate information to investors to reduce the irrational behavior.Originality – This study modifies the objective of Islamic banks’ stock prices in Indonesia by elaborating rational and irrational factors as the determinants of stock prices.